ENHANCEMENT OF THE IMMUNE RESPONSE OF CHICKENS VACCINATED WITH ADJUVANTED LIVE NEWCASTLE DISEASE VIRUS VACCINE - Yasmin Shawky; Ashraf Hussein; Owais G. A. Salman; Amal A. M. Eid (Slovenian Veterinary Research, 2023)
The poultry industry depends heavily on immunization, particularly with live attenuated vaccines. These vaccines are commonly not adjuvanted and can be either injected or delivered in birds’ mucosa. In the current study we evaluated the protective efficacy of adjuvanted and non-adjuvanted live Newcastle disease virus (LaSota strain) vaccines. Three non-adjuvanted live NDV vaccines were used to vaccinate three groups of chickens. The same immunizations were administered to three additional groups employing adjuvant technology where a mucosal adjuvant (Montanide TM IMS 1313 nanoparticles) was used. Under experimental conditions, humoral and cellular immune responses were assessed, and challenge test was done for evaluation of the vaccine efficacy in the vaccinated chickens. RT qPCR was used for determination of viral shedding in oropharyngeal swabs of challenged chickens. Mucosal nanoparticles adjuvanted live NDV vaccines significantly improved the antibody titer and the cell mediated immune response in comparison with the non-adjuvanted ones. In the challenged chicken groups with highly virulent NDV sub-genotype VIId at the third week post vaccination, the Montanide adjuvanted vaccines were fully protective and prevention of virus shedding was also noticed while the protection rate of non-adjuvanted vaccines ranged from 90% to 100% and the virus shedding was reduced. The study indicated that, efficacy of live vaccines could be improved by using Montanide™ IMS 1313 nanoparticles adjuvant in a model of mucosal delivery of live NDV vaccine in chickens.